Metacarpal Stress Fracture Is Not an Uncommon Condition in Adolescent Racket Athletes. (8th February 2020) - Nishikawa, Karen; Kimura, Yuka; Chiba, Daisuke; Sasaki, Norihiro; Sasaki, Shizuka; Nishikawa, Shinji; Ishibashi, Yasuyuki
Abstract : Background . Stress fractures of the metacarpal bones are considered uncommon. We report on 11 adolescent athletes with these stress fractures, successfully treated with cessation of sports activities. Representative case presentation . In case 1, a 15-year-old male tennis player presented with right hand pain of 4-week duration without an acute trauma history. Tenderness existed on palpation along the dorsal and proximal second metacarpal bone. Plain radiographs demonstrated a periosteal reaction on the proximal shaft of the second metacarpal. Racket swinging was suspended. He returned to competitive tennis 2 months after the initial visit and continues to participate without symptoms. In case 2, a 16-year-old male boxer presented with right hand pain of 2-week duration that arose while punching. Acute trauma history was absent. Tenderness existed on palpation over the third metacarpal of the right hand. Plain radiographs demonstrated no periosteal reaction or fracture line. MRI showed a high signal on the third metatarsal bone on fat suppression and a low signal on T2-weighted images. Nonoperative treatment was initiated without external fixation, and punching was suspended. He returned to boxing 1 month after the initial visit without symptoms. Conclusions . The current case series of metacarpal stress fractures demonstrate that this condition is not as rare as previously reported. Metacarpal stress fractures are generally ignored since the clinical and radiological findings are mostly unclear. If an athlete experiences hand pain without acute onset during sports activities, especially in racket sports, the presence of a metacarpal stress fracture should be assessed by MRI.